Reducing Discomfort After Cesarean Birth Using Abdominal Binders. Issue 6 (November 2019) - Tussey, Christina; Kelly, Lesly A.; Oja, Kenneth J.; Bay, R. Curtis; Makarova, Natasha
Abstract: Purpose: The purpose of this study was to evaluate potential benefits of use of an abdominal binder after cesarean birth. Study Design and Methods: A randomized controlled trial was conducted at a Magnet-designated, academic medical center in the southwest United States. English- and Spanish-speaking adult women scheduled for an elective cesarean birth were randomized to the intervention or control group. Outcomes were measured for the first 48 hours postoperatively, including pain, medication use, and self-reported symptom distress. Results: Randomization resulted in balanced groups. Women who used the abdominal binder after cesarean birth reported a decrease in pain after ambulation, whereas women in the control group reported an increase in pain after ambulation ( p < .001). Women in the binder group reported less distress on the Breathe and Cough items of the Symptom Distress Scale than those in the control group. On postoperative day 2, women in the binder group used more ibuprofen ( p = .002) and acetaminophen ( p = .027) than the control group. Clinical Implications: Use of an abdominal binder by women after cesarean birth can decrease pain, potentially enhancing speed of postoperative recovery. As a nursing intervention, abdominal binders may offer women a safe nonpharmacologic option to provide postoperative comfort. Abstract : There is great interest in options for enhancing pain relief measures that do not involve opioids for women after cesarean birth. This randomized controlled trial evaluated use of an abdominal binder for women after cesarean birth. Findings suggest abdominal binders can decrease pain related to ambulation, potentially enhancing postoperative recovery. As a nursing intervention, abdominal binders may offer women a safe nonpharmacologic option to provide comfort.